PERAN KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KOMITMEN ANGGOTA PADUAN SUARA MAHASISWA KABINET CHITRASWAA RASIKA UNIVERSITAS BINA BANGSA - Fiwasifi Isyiya; Eka Susilawati; Fithrotul Kamilah; Rizqi Fitrianti; Meiby Zulfikar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The commitment of student organization members is influenced by the communication patterns they employ. The Chitraswara Rasika Cabinet Student Choir of Bina Bangsa University faces challenges in maintaining the active participation of its members. This research used descriptive qualitative methods with Herbert Blumer's symbolic interactionism theory. The results indicate that two-way communication, emotional involvement, and organizational symbols strengthen affective and normative commitment. The main obstacles are sudden information and minimal feedback. It is recommended that organizations establish more transparent and participatory communication to maintain member commitment.